Economics in the long run : New Deal theorists and their legacies, 1933-1993 - Rosenof, Theodore (University of North Carolina Press, 1997)
Though understandably preoccupied with the immediate problems of the Great Depression, the generation of economists that came to the forefront in the New Deal Era of the 1930s also looked ahead to the long-term consequences of the crisis and proposed various solutions to prevent its recurrence. Theodore Rosenof examines the long-run theories and legacies of four of the leading members of this generation: John Maynard Keynes of Great Britain, who influenced the New Deal from afar; Alvin Hansen and Gardiner Means, who fought over the direction of New Deal policy; and Joseph Schumpeter, an opponent of the New Deal.